2023
DOI: 10.1177/17539447231160319
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with drug therapy problems among hypertensive patients at hypertension clinic of Mbarara Regional Referral Hospital, Uganda: a |cross-sectional study

Abstract: Background: Despite the use of safe and effective conventional drugs, drug therapy problems (DTPs) pose a threat to the successful management of hypertension. DTPs are of a great concern in health care because of their serious consequences such as poor quality of life, increased health care costs, morbidity and mortality. However, there is no published information regarding the prevalence of DTPs and associated factors among hypertensive patients in Uganda. Objective: The aim of the study was to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This was lower than the study results obtained at Gebretsadik Shawo General Hospital, 84.4%, 11 and Malaysia, 90.5%. 15 However, it was higher than other study results reported from Dil-Chora Referral Hospital, 71.2%, 10 Ayder comprehensive specialized hospital, 55.6%, 12 Uganda, 61.8%, 16 and Indonesia, 57%. 17 The different rates of prevalence could be caused by variations in the study period, the number of professionals participating in DTP identification, and the size of the study population.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This was lower than the study results obtained at Gebretsadik Shawo General Hospital, 84.4%, 11 and Malaysia, 90.5%. 15 However, it was higher than other study results reported from Dil-Chora Referral Hospital, 71.2%, 10 Ayder comprehensive specialized hospital, 55.6%, 12 Uganda, 61.8%, 16 and Indonesia, 57%. 17 The different rates of prevalence could be caused by variations in the study period, the number of professionals participating in DTP identification, and the size of the study population.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, the second most common DTP (29.54%) was non-compliance with antihypertensive medications, which was lower than the results of studies done in Dil-Chora Referral Hospital, which was 32.8%. 10 However, this was higher than the findings of studies conducted at Adama Hospital Medical College (19.5%), 19 Uganda (19.1%), 16 and Indonesia (13.6%). 20 The difference in the prevalence of non-compliance with medications might be due to the presence of co-morbid conditions, polypharmacy, accessibility to health facilities, and differences in knowledge between people.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, 38 studies [ 45 50 , 52 , 54 64 , 66 74 , 76 , 78 , 79 , 82 84 , 89 , 90 , 92 94 ] reported the occurrence of ADEs in the outpatient setting, and four studies [ 53 , 75 , 77 , 81 ] reported ADEs in the community setting. Majority of included studies [ 18 22 , 27 29 , 32 34 , 36 , 37 , 40 , 41 , 43 , 45 – 48 , 52 , 54 60 , 62 65 , 67 , 70 , 72 – 74 , 76 , 79 , 81 , 82 , 89 , 90 , 92 94 ] were carried out on adult population (aged ≥ 18 years) ( n = 46), while 18 studies were conducted among all age groups (aged 0–100 years) [ 23 , 24 , 30 , 50 , 51 , 61 , 66 , 68 , 69 , 71 , 75 , 77 , 78 , 84 88 ], 12 studies [ 25 ...…”
Section: Resultsmentioning
confidence: 99%
“…Examples of DTPs include the employment of unneeded or ineffective medications, the lack of prescribed medications, adverse drug reactions (ADRs), and medication non-adherence ( 4 ). The significance of DTPs in health care cannot be underestimated due to their grave consequences, such as diminished quality of life, escalated health care expenditures, and fatalities associated with medication use ( 5 ). In the United States, the projected yearly expenditure attributed to drug-related morbidity and mortality resulting from suboptimal drug therapy surpasses $520 billion ( 6 ).…”
Section: Simple Challenge – Complex Problemmentioning
confidence: 99%